(untitled) (JOURNAL OF ADVANCES IN PHYSICS, 2024)
From ontological considerations alone, a new revolutionary quantum dynamical-materialist dialectical (Quantum Dialectics or QD) perspective of space-time-matter-motion achieves a new quantitative mass-energy-velocity relation for any ponderable fundamental particles. This new relation, based on the quantum uncertainty principle, gives the mass m of any free fundamental particle at its origin, in terms of the inverse cube of its velocity v. This quantitative relation is different and is a negation of the one derived from mechanical-metaphysical (Classical Mechanics or CM) approach since Isaac Newton and its relativistic post-quantum formulation of Albert Einstein. This new mass-energy-velocity relation is in conformity with known knowledge and is appropriately substantiated by the recent reports that “high-energy photons of gamma radiation from a distant galaxy arrived at Earth four minutes after lower-energy photons, although they were apparently emitted at the same time”; and another saying that “the time delays of gamma-ray photons are inversely proportional to their energy”. These findings would contradict Einstein’s theory of relativity, which says that all photons (particles of light) must move at the same speed c. QD considers matter-antimatter particle pairs in their elementary virtual forms and kinetic motion as an eternal quantum dynamical process of existence and non-existence (Being-Nothing) arising from abstract space and abstract time in a contradiction to each other. The virtual particles can transition to real particles through quantum tunnelling or when equivalent energy becomes available. Any existence in this view is a contradiction; vulnerable to change, motion, evolution, development etc. The aggregation of the elementary particles and their motions mediated by chance and necessity, give rise to the phenomenology of this infinite, eternal and ever-changing universe. The CM approach on the contrary is based on epistemology and considers that matter (ordinary + light) and motion have an esoteric origin from the mystery of the single act of creation by God; of a finite universe in the finite past; where the premise of conservation laws and “ex nihilo nihil fit” prevail. In its relativistic version, this approach makes a fundamental difference between ponderable matter and light and in fact question the existence of particulate matter. Two axiomatic assumptions, one by Newton of one-sided universal gravitational attraction and the other by Einstein that the velocity of light c is an absolute and universal constant has brought in unphysical objects and phenomena into scientific discourse leading to century-long confusion and scholastic debates among the physicists; with no end in sight!